2008
DOI: 10.1111/j.1096-3642.2008.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and mineral composition of serpulid tubes (Polychaeta, Annelida)

Abstract: We have studied the tube ultrastructure of 44 recent species from 36 serpulid genera. Twelve distinct ultrastructures are identified. Serpulids possess very diverse tube ultrastructures, in contrast with the traditional point of view. Most species show single-layered tubes, but 34% of these species have between two and four ultrastructurally different layers. Tubes are mostly bimineralic, and are composed of aragonite and calcite; however, one of the polymorphs is always dominant. All the studied single-layere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
173
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 107 publications
(180 citation statements)
references
References 18 publications
2
173
3
2
Order By: Relevance
“…reveals a striking difference in the complexity of tube ultrastructures between the two major clades. The complex oriented structures and the oriented prismatic structures restricted to the clade A (Vinn et al, 2008b;Vinn and Kupriyanova, 2011: fig. 1) seem to be derived from isotropic structures that are considered to be plesiomorphic (Vinn, 2013c).…”
Section: Tube Ultrastructures: a New Tool In Serpulid Systematics?mentioning
confidence: 99%
See 4 more Smart Citations
“…reveals a striking difference in the complexity of tube ultrastructures between the two major clades. The complex oriented structures and the oriented prismatic structures restricted to the clade A (Vinn et al, 2008b;Vinn and Kupriyanova, 2011: fig. 1) seem to be derived from isotropic structures that are considered to be plesiomorphic (Vinn, 2013c).…”
Section: Tube Ultrastructures: a New Tool In Serpulid Systematics?mentioning
confidence: 99%
“…Vinn et al (2008b) examined 44 species belonging to 36 genera and showed that 47% of studied species possess a unique combination (ultrastructural types and their arrangement into layers) of tube characters. Most advanced and highly ordered types of structures are difficult to explain from the point of the classic for serpulids "granular secreting" model (Neff, 1971), so a matrix-mediated model of biomineralisation was proposed .…”
Section: Tube Ultrastructures: a New Tool In Serpulid Systematics?mentioning
confidence: 99%
See 3 more Smart Citations